Platelet Malondialdehyde in Cardiovascular Disease: Effect of Prosthetic Heart Valves and Cardioactive Drugs on Production - Sullivan, Jay M; Taylor, J Charles; Samaha, Joseph K; With the technical assistance of; Lamar, Patti; Patrick, Darrell R (Thrombosis and Haemostasis, 1980)
Malondialdehyde (MDA), a product of platelet lipid peroxidation, was measured in human platelet-rich plasma. Levels of 3.19 n moles/109 platelets ± 0.40 S.E. in 11 patients with prosthetic heart valves were elevated (p<0.25) compared to 17 normal subjects (2.09 ± 0.13 n moles/109 platelets). Reduced production (1.44 ± 0.28 n moles/109 platelets, p<0.5) was found in 10 patients with unstable angina. Normal levels were found in patients with mitral stenosis, cardiomyopathy or hypertension. Usual serum levels of drugs used in cardiac treatment reduced MDA levels as follows: acetaminophen, 47% (p<.01); aspirin, 58% (p<.05); furosemide, 32.6% (p<.005), and sulfinpyrazone, 41% (p<.05). Digoxin, dipyridamole, heparin, hydrochlorothiazide, lidocaine, nitroglycerin, procainamide, propranolol, quinidine, or warfarin had no significant effect at therapeutic concentrations. None of the drugs explained the enhanced production in patients with prosthetic valves while analgesic therapy could explain the decreased levels in other cardiacs. The half-time of platelet survival, measured by suppression of malondialdehyde production, was 3.2 ± 0.24 days in 9 normal subjects but could not be measured reliably in most patients because of multiple drug therapies. We conclude that the blood platelets of patients with prosthetic heart valves differ from those of normal subjects in their capacity to release malondialdehyde after stimulation with n-ethylmaleimide. Additionally, we find that inhibition of malondialdehyde production by several pharmacologic agents limits the usefulness of this method for the measurement of platelet survival in cardiac patients.
Keywords: Blood platelets; Cardiovascular diseases; Heart valve prosthesis; Lipid peroxidation; Malondialdehyde; Prostaglandins